2018
DOI: 10.1109/jsac.2017.2774706
|View full text |Cite
|
Sign up to set email alerts
|

A Fixed-Scale Pixelated MIMO Visible Light Communication System

Abstract: Visible light communication (VLC) systems take advantage of ubiquitous light-emitting diodes (LED) and leverage existing illumination infrastructure to provide broadband optical communication links. Multiple-input multiple-output (MIMO) VLC systems are among the well-studied topics in VLC research. However, most traditional MIMO VLC systems require accurate alignment and have to adjust to different magnifications at various link distances. Consequently, the alignment and calibration modules increase the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Since OCC operation is generally bounded by both the LOS path and the limitations of cameras, there are several issues that need addressing: directionality, focusing, alignment and distance. In [90], a pixelated MIMO scheme with a TX (an array of LEDs) fitted with a collimating lens was experimentally investigated for transmission in the angular domain rather than in the space domain. A series of time-varying coded (i.e., Raptor code) images were captured and decoded using a camera, which was focused at infinity, thus achieving a throughput of 30 bit/frame at a link span of 1 m. In addition, this scheme is robust against misalignment, camera focus and orientation.…”
Section: Interference Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since OCC operation is generally bounded by both the LOS path and the limitations of cameras, there are several issues that need addressing: directionality, focusing, alignment and distance. In [90], a pixelated MIMO scheme with a TX (an array of LEDs) fitted with a collimating lens was experimentally investigated for transmission in the angular domain rather than in the space domain. A series of time-varying coded (i.e., Raptor code) images were captured and decoded using a camera, which was focused at infinity, thus achieving a throughput of 30 bit/frame at a link span of 1 m. In addition, this scheme is robust against misalignment, camera focus and orientation.…”
Section: Interference Mitigationmentioning
confidence: 99%
“…Complex modulation schemes (including multi-level and multi-carrier) as well as WDM technologies can be used to increase the data throughput in OCC systems [90,133]. In addition, cameras with increased resolution and the development of more powerful image processing algorithms will enhance the efficiency and robustness of OCC [17,37].…”
Section: Advanced Modulation and Communication Mediummentioning
confidence: 99%
“…The low-priority data was modulated onto the highfrequency components while the high-priority data was modulated on the low-frequency components. The effectiveness of the proposed scheme in [87] In addition to the trend of improving the data rate and transmission distance, efforts are made to improve the system design for OCC, e.g., a spatial-angular modulation technique was developed in [89] by using pixelated MIMO systems to simplify the receiver design. Furthermore, an image sensor with the MIMO technique was used in [90] to reduce the inter-channel interference between the RGB signals.…”
Section: Non-standardized Techniquesmentioning
confidence: 99%
“…Furthermore, it was showed that the computation burden of decentralized power allocation algorithms is less when compared with centralized power allocation algorithms. Recently, a fixed‐scale pixelated MIMO VLC was proposed in the work of Han and Hranilovic . The transmitter consists of array of emitters with collimating lens, which enables space to angle mapping of data.…”
Section: Techniques For Data Rate Improvement In Visible Light Communmentioning
confidence: 99%
“…Recently, a fixed-scale pixelated MIMO VLC was proposed in the work of Han and Hranilovic. 92 The transmitter consists of array of emitters with collimating lens, which enables space to angle mapping of data. Focusing the receiver at infinity, a sequence of time-varying images were captured by a high-speed camera.…”
Section: Data Rate Improvements Through Multiple Input Multiple Outputmentioning
confidence: 99%